Osteoanabolic Implant Materials for Orthopedic Treatment. Issue 14 (26th April 2016) - Ding, Yun‐Fei; Li, Rachel W.; Nakai, Masaaki; Majumdar, Trina; Zhang, Dong‐Hai; Niinomi, Mitsuo; Birbilis, Nick; Smith, Paul N.; Chen, Xiao‐Bo
Abstract : Osteoporosis is becoming more prevalent due to the aging demographics of many populations. Osteoporotic bone is more prone to fracture than normal bone, and current orthopedic implant materials are not ideal for the osteoporotic cases. A newly developed strontium phosphate (SrPO4 ) coating is reported herein, and applied to Ti‐29Nb‐13Ta‐4.6Zr (wt%), TNTZ, an implant material with a comparative Young's modulus to that of natural bone. The SrPO4 coating is anticipated to modulate the activity of osteoblast (OB) and osteoclast (OC) cells, in order to promote bone formation. TNTZ, a material with excellent biocompatibility and high bioinertness is pretreated in a concentrated alkaline solution under hydrothermal conditions, followed by a hydrothermal coating growth process to achieve complete SrPO4 surface coverage with high bonding strength. Owing to the release of Sr ions from the SrPO4 coating and its unique surface topography, OB cells demonstrate increased proliferation and differentiation, while the cellular responses of OC are suppressed, compared to the control case, i.e., bare TNTZ. This TNTZ implant with a near physiologic Young's modulus and a functional SrPO4 coating provides a new direction in the design and manufacture of implantable devices used in the management of orthopedic conditions in osteoporotic individuals. Abstract : An orthopedic implant material specifically designed for osteoporotic bone fractures is reported herein. A strontium phosphate (SrPO4 ) coating applied to a bone‐mimicking low elastic modulus Ti alloy, TNTZ, results in upregulating the growth of osteoblasts and downregulating that of osteoclasts. This functional SrPO4 coating provides a new direction in the design and manufacture of implantable devices used in the treatment of osteoporotic bone fractures.